Strategi Peningkatan Kemampuan Personel Paspampres dalam Tugas Pengamanan Wakil Presiden Republik Indonesia - Saputra, Angga Prawira Arief; Putro, Resmanto Widodo; J, Thomas Gabriel (Universitas Pahlawan Tuanku Tambusai, 2025)
The President and Vice President of the Republic of Indonesia are representatives of the high state institutions that carry out executive functions as head of state, head of government, commander of the Indonesian Army and other functions. The security of the President and Vice President is one of the Indonesian Military Operations Other Than War which is delegated to the Presidential Security Forces under the responsibility of the Indonesian Army Commander which is carried out both domestically and abroad. The security of the Vice President is carried out by Group B with full responsibility to personnel who are strictly selected. However, in implementation it has not been fully optimal, especially in terms of facilities and mastery and skills in self-defense, shooting, foreign languages and information technology and teamwork. The purpose of this study is to analyze the readiness and capabilities of Paspampres Group B personnel in carrying out their duties. This study uses a descriptive qualitative method by collecting information from various sources and analyzing it theoretically and in accordance with applicable regulations. The findings of this study indicate the need for improvements in various fields, especially in terms of facilities and quality of personnel in mastering shooting skills, self-defense, mastery of foreign languages and information technology and teamwork through structured and sustainable training management.